Focus on Nintedanib in NSCLC and Other Tumors - Manzo, Anna; Carillio, Guido; Montanino, Agnese; Costanzo, Raffaele; Sandomenico, Claudia; Rocco, Gaetano; Morabito, Alessandro (Frontiers in Medicine, 2016)
Nintedanib is a new triple angiokinase inhibitor that potently blocks the proangiogenic pathways mediated by vascular endothelial growth factor receptors, platelet-derived growth factor receptors, and fibroblast growth factor receptors. Evidence about its efficacy in addition to second-line chemotherapy in non-small cell lung cancer (NSCLC) has been produced by two large randomized phase III clinical trials (LUME-Lung 1 and LUME-Lung 2), conducted in patients with pretreated NSCLC, without major risk factors for bleeding. In the LUME-Lung 1, the addition of nintedanib to docetaxel significantly improved progression-free survival, which was the primary end point of the trial (3.4 vs. 2.7 months, hazard ratio: 0.79; p = 0.0019). Furthermore, a significant improvement in median overall survival (from 10.3 to 12.6 months) was observed in patients with adenocarcinoma histology, with a greater advantage in patients who progressed within 9 months after start of first-line treatment (from 7.9 to 10.9 months) and in patients who were most refractory to first-line chemotherapy (from 6.3 to 9.8 months). Adverse events were more common in the docetaxel plus nintedanib group, and they included diarrhea and increased liver enzymes, while no statistically significant increase in the incidence of bleeding and hypertension events by the addition of nintedanib was observed. On these bases, the combination of docetaxel and nintedanib can be considered a new option for the second-line treatment for patients with advanced NSCLC with adenocarcinoma histology. Future challenges are the identification of predictive factors to help the decision of using nintedanib in eligible patients.